Real time human emotion monitoring based on bio-signals - Tangtisanon, Pikulkaew (My University, 2018)
Nowadays, medical technologies are rapidly improved leading to an increasing of life expectancy that caused ageing society problems. The most vital issue for elders is a health problem in both physical and mental aspect. This paper focuses on emotional monitoring and warning system using human Bio-signals in real time. The signals come from galvanic skin response and heart rate sensor that attached with a wristband wearing by the elders. The two signals are sent to a server as inputs, calculated using Fuzzy set variable model then return emotion and health status of the elder as outputs stored in the server. The proposed system is run based on ubiquitous computing so caretakers can monitor for the elder’s emotion in real time anywhere, any time. Moreover, the caretakers also get automatically alerts from the system in a case that the system returns an irregular health status of the elders. Experimental results show that the proposed system was run with a high accuracy rate.
Keywords: Bio-signal; Fuzzy; GSR sensor